2020
DOI: 10.1507/endocrj.ej18-0558
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic values of thyroglobulin in lymph node fine-needle aspiration washout: a systematic review and meta-analysis diagnostic values of FNA-Tg

Abstract: Thyroglobulin measurement in the needle washout after fine-needle aspiration (FNA-Tg) served as an important measurement for suspicious recurrent or metastatic lesions. We conducted a pooled analysis to evaluate the diagnostic accuracy of FNA-Tg and searched electronic databases for original articles in English from 1993 through 2017. Finally, a total of 22 studies containing 2,670 lymph nodes (LNs) that enrolled participants with suspicious neck LNs during thyroid nodule workup or papillary thyroid cancer (PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
1
28
0
2
Order By: Relevance
“…Cervical LNM was suggested if there were the following features, for ultrasound: absence of an echogenic hilum, round shape, microcalcification, peripheral blood flow on color Doppler images, or cystic changes (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18); for CT: area with clear evidence of nonfat, low-density, or liquid components; largest diameter >15 mm at level II and >10 mm at other levels; and ratio of the longest to smallest diameter ≤2.…”
Section: Treatment Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cervical LNM was suggested if there were the following features, for ultrasound: absence of an echogenic hilum, round shape, microcalcification, peripheral blood flow on color Doppler images, or cystic changes (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18); for CT: area with clear evidence of nonfat, low-density, or liquid components; largest diameter >15 mm at level II and >10 mm at other levels; and ratio of the longest to smallest diameter ≤2.…”
Section: Treatment Principlesmentioning
confidence: 99%
“…Ultrasound-guided fine needle aspiration biopsy cytology (FNAB-C) and core needle biopsy tissue (CNB-T) play an important role in evaluating cervical lymph node status in thyroid cancer and head and neck squamous cell carcinoma (SCC), respectively (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, the value of FNAB-C is greatly limited if the number of specimens is small or the specimens are obtained from cystic lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last meta-analysis based on the largest published studies found that a FNAB-Tg cut-off value of 1 ng/mL had highest sensitivity and 40 ng/mL had highest specificity [9]. An FNAB-Tg cut-off value has not been unanimously established.…”
Section: Cut-off Levelsmentioning
confidence: 99%
“…This assay was first proposed by Pacini et al, and despite being recommended by many guidelines the technique is not standardized [8]. There are considerable differences between various diagnostic centres regarding the methodology of measurement of Tg levels as well as cut-off values for FNAB-Tg in positive cases (varying from 0.2 ng/mL to 100 ng/mL in different studies) [9].…”
Section: Introductionmentioning
confidence: 99%